Austrochthonius chilensis subsp. transversus Beier 1964 ... - Mahnert, Volker; Iorio, Osvaldo Di; Turienzo, Paola; Porta, Andres (Zenodo, 2011)
Austrochthonius chilensis transversus Beier, 1964 RÍO NEGRO: El Bolsón, Mt. Piltriquitron (type locality), “Fallaub und aus Moos in Wäldern von Maytenus boaria, Berberis darwini, Nothofagus antarctica, Nothofagus pumilio, Mulinum-Lomatia- Vegetation, von 920 bis1500 m ” (Beier 1964) (HMHN, NHMW) (Ceballos & Rosso de Ferradás 2008a); Río Negro (Vitali-di Castri 1975); El Bolsón, Valle del Río Azul, “aus Moos von Felsen” (Beier 1964) (NHMW) (Ceballos & Rosso de Ferradás 2008a); CHUBUT: Lago Espejo, El Hoyo, 1000 m, aus Moos von Rinde und Boden im Nothofagus antarctica Wald, nahe am See” (Beier 1964) (NHMW) (Ceballos & Rosso de Ferradás 2008a). ... : Published as part of Mahnert, Volker, Iorio, Osvaldo Di, Turienzo, Paola & Porta, Andres, 2011, Pseudoscorpions (Arachnida) from Argentina. New records of distributions and habitats, corrections and an identification key, pp. 1-30 in Zootaxa 2881 on page 8, DOI: 10.5281/zenodo.205780 ...